The Influence of Financial Management Practices, Internal Control System, Human Resources Competency and Information Technology on The Quality of Mosque Financial Reports in Langsa City - Rahmat Daim Harahap; Zainarti Zainarti; Aziz Aulia; Husni Husni (Journal of Management and Business Innovations, 2020)
This study aims to see the effect of Financial Management Practices, Internal Control Systems, Human Resource Competence and Information Technology Utilization on the quality of financial reports partially and simultaneously. To examine the influence of Financial Management Practices, Internal Control Systems, Human Resources Competence and Information Technology Utilization on the Quality of Financial Statements partially and simultaneously. The sample in this study was taken using the saturated sample method or census. There are 47 questionnaires that can come up. The analysis used in this study is multiple linear regression analysis using SPSS software version 20.0. The results showed that the variables partially affect the quality of financial management practices and human resource competencies and the variables of control systems and the use of information technology had no effect on the quality of financial reports. However, simultaneously Financial Management Practices, Internal Control Systems, Human Resources Competence and Utilization of Information Technology affect the quality of financial reports. This research helps that it is necessary to hold a training program for mosque administrators in order to increase the competence of human resources and to improve the quality of mosque financial reports, besides that the mosque must support the existence of information technology at the mosque so that it can make the mosque more updated or can always be accessed by congregation. And with that the financial reports will automatically be of higher quality.Keywords: Competence of human resources, financial management practices, internal control systems, quality of financial statements, utilization of information technology